2019
DOI: 10.1111/apa.14950
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of parental experiences caring for their hospitalised medically fragile infants

Abstract: AimTo synthesise and summarise evidence from published research articles regarding parental experiences caring for their hospitalised medically fragile infant.MethodsWe searched four electronic databases in April 2018 using three main concepts individually and in combination: infant, medically fragile, parents. We examined articles about experiences of parents caring for the medically fragile infant in a hospital setting. We conducted thematic analysis on the 34 included articles.ResultsParents experienced hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Currently, family integrated care is getting implemented, a form of care in which parents provide all except the most advanced medical care for their infants [145][146][147]. In general, more parental involvement is associated with better outcomes of family and infant [148][149][150].…”
Section: Intervention In Infants Admitted To the Neonatal Intensive Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, family integrated care is getting implemented, a form of care in which parents provide all except the most advanced medical care for their infants [145][146][147]. In general, more parental involvement is associated with better outcomes of family and infant [148][149][150].…”
Section: Intervention In Infants Admitted To the Neonatal Intensive Cmentioning
confidence: 99%
“…Medically fragile infants and their parents experience high levels of stress [148][149][150]. Early intervention, generally called developmental care, aims at the promotion of parentinfant interaction, stress reduction and provision of a supportive environment.…”
Section: Intervention In Infants Admitted To the Neonatal Intensive Cmentioning
confidence: 99%
“…One could wonder if enough attention is paid to trauma stressors during hospitalization [43] . It is recommended to provide sufficient information about support resources at discharge, including contact details of patient associations and primary care providers [44] .…”
Section: Personal and Environmental Factorsmentioning
confidence: 99%
“…While some parents find a meaningful sense of purpose in life and show profound resilience, others report feeling overwhelmed and exhausted by the acute and chronic caregiving pressures thrust upon them and subsequently endure poor health-related quality of life ( Hatzmann et al, 2008 ). Caring for a child with special healthcare needs has been associated with elevated stress, physical and mental health problems, grief and trauma, sleep deprivation, employment loss, financial hardship, and social isolation ( Cousino & Hazen, 2013 ; Kuo et al, 2011 ; Mackay et al, 2019 ; Miodrag et al, 2015 ; Smith et al, 2013 ). A recent systematic review and meta-analysis of 26 studies found that caregivers, specifically mothers, of children with chronic illness experience clinical depression and anxiety at significantly higher rates than those with healthy children ( Cohn et al, 2020 ).…”
Section: Health and Service Needs Of Children With Medical Complexitymentioning
confidence: 99%